Suboptimal B‐cell antigen receptor signaling activity in vivo elicits germinal center counterselection mechanisms. Issue 2 (2nd December 2014) - Königsberger, Sebastian; Weis, Vanessa; Prodöhl, Jan; Stehling, Martin; Hobeika, Elias; Reth, Michael; Kiefer, Friedemann
<x xml:space="preserve">Abstract</x> Syk and Zap‐70 constitute a closely related nonreceptor protein tyrosine kinase family, of which both members are functionally indispensable for conferring their respective antigen receptors with enzymatic activity. In this study, we analyze the impact of altering BCR signaling output on B‐cell germinal center (GC) fate selection by constitutive, as well as inducible, monoallelic Syk kinase loss in the presence of a Zap‐70 knock‐in rescue allele. Cre‐mediated Syk deletion in Sykflox/Zap‐70 B cells lowers pErk, but not pAkt‐mediated signaling. Surprisingly, the use of a B‐cell‐specific constitutive mb1‐cre deleter mouse model showed that a small cohort of peripheral Sykflox/Zap‐70;mb1‐cre B cells efficiently circumvents deletion, which ultimately favors these Syk‐sufficient cells to contribute to the GC reaction. Using a developmentally unbiased Sykflox/Zap‐70;mb1‐creERT2 approach in combination with an inducible tdRFP allele, we further demonstrate that this monoallelic deletion escape is not fully explained by leakiness of Cre expression, but is possibly the result of differential Syk locus accessibility in maturing B cells. Altogether, this underscores the importance of proper Syk kinase function not only during central and peripheral selection processes, but also during GC formation and maintenance.